Association between self-worth and health promotion behaviors among older adults living in the community: a cross-sectional study - Fatemeh Zarghami; Roghayeh Sadegi; Parvin Sarbakhsh; Sina Pakmehr; Vahid Pakpour (BMC Public Health)
Abstract Background Population aging is one of the most significant global social changes, making the improvement of the health and quality of life for the elderly a key health priority. The adoption of health promotion behaviors and having self-worth are effective approaches to maintain the health of older people. The current study aimed to investigate health promotion behaviors and their relationship with self-worth among the elderly in Tabriz, Iran. Methods This cross-sectional study recruited 427 older people, who lived in Tabriz in 2022. The participants were selected using multistage random cluster sampling. The Health Promotion Activities of Older Adults Measure, and the Contingencies of Self-Worth Scale were used for collecting the data. Descriptive and inferential statistics methods were applied to the data. Results The results showed a moderate mean score of health promotion behaviors (93.25 ± 15.39) and a low mean score of self-worth (79.30 ± 10.29) for the participants. The multivariate linear regression analysis showed a significant relationship between health promotion behaviors and self-worth among the older adults (p < 0.01). Therefore, self-worth could predict about 3.7% of the variance of health promotion behaviors among this population (R 2 = 0.037, t = 4.01). Although the association was statistically significant, the explained variance was low, indicating that self-worth had a limited predictive value for health promotion behaviors in this sample. Conclusions While self-worth showed a modest correlation with health promotion behaviors, multivariable analysis revealed socioeconomic factors as stronger predictors. Interventions should address structural determinants alongside psychosocial factors to improve elderly health. Future studies are needed to explore causal pathways between self-worth and health behaviors in aging populations.